Critical Thinking and Nurses' Caring Behavior in Clinical Practice: A Cross-sectional Study - Ailsa Ayu Fadhilla; Nurfika Asmaningrum; Dodi Wijaya; Nurul Arifah; Dwi Yoga Setyorini; Desy Listyaningrum (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background: Caring behavior is essential in nursing professionalism and is linked to the quality of nursing care. Nurses are responsible for providing holistic, patient-centered healthcare that includes various dimensions of well-being. However, nursing practice often lacks a holistic approach, especially as patient cases become more complex. Balancing critical thinking skills with caring behavior is crucial to meet the demands of nursing practice. Objective: To examine the association between critical thinking skills and caring behavior among ward inpatient nurses at Perkebunan Jember Klinik Hospital. Methods: A cross-sectional correlational study was conducted among all 82 nurses in tbe inpatient ward through total sampling. Critical thinking ability were measured using a NCT-4 Practice, and Caring behavior were assessed using Caring Behavior Questionnaire. Descriptive statistics were calculated for participant characteristics and study variables. The association between critical thinking skills and caring behavior was tested using Kendall’s Tau C (a =0,05). Results: Participants had a median age of 35 years and the work experience of nurses 10,5 years, were most female (76,8%), with the nurses’ highest education is in the nursing profession (72%) and the majority nurses are married (93,9%). The majority partisipants also attended the training (91,5%). Kendall’s Tau C indicated a statistically significant, weak correlation between critical thinking skills and caring behavior, with moderate critical thinking skills tending to be associated (|τ| = 0,376, p = 0,000), with caring conduct that is nonetheless considered to be deficient Conclusion: Critical thinking skills were significantly correlation with caring behavior among ward inpatient nurses.The development of evidence-based practice and the enhancement of clinical reasoning capacity through training and independent literature exploration are recommended to improve daily clinical critical thinking skills.